Nonlinear Free Vibration of Laminated Composite and Sandwich Plates Using Multiquadric Collocations. (2015) - Solanki, Manoj Kumar; Mishra, Sabin Kumar; Shukla, K.K.; Singh, Jeeoot
Abstract: The paper examines the nonlinear free vibration response of shear deformable laminated composite and sandwich plates. The mathematical formulation of the actual physical problem of the plate is presented utilizing shear deformation theories and von Karman nonlinear kinematics. A meshless technique based on multi quadric radial basis function (MQRBF) is used for analysis of the problems. Using standard computational software of MATLAB 7, the eigenvalue problem is solved to get the eigen frequencies and eigen vectors. Several numerical results depicting the non dimensional frequency parameter of the isotropic, orthotropic, laminated and sandwich plates are presented. In order to check the accuracy of the present method, the results are compared with existing one in the literature. The effects of aspect ratio, span to thickness ratio, orthotropy ratio of the material and fiber orientation on the frequency are also studied.